Model Akuntabilitas dan Transparansi Pengelolaan Hibah Masjid Berbasis Kearifan Lokal Masyarakat - Piola, Marina Paramita S.; Mauli, Siti Awalanda (Universitas Gorontalo, 2024)
This research decisively reveals a robust model of accountability and transparency in the management of mosque grants, firmly based on the local wisdom of the Gorontalo community. Using qualitative methods, the study employs a range of effective data collection techniques, including interviews, observations, and documentation at mosques that receive grants in Gorontalo City. The results demonstrate that accountability and transparency in managing mosque grant funds are effectively upheld through straightforward record-keeping, deeply embedded in local values such as trustworthiness, patience, honesty, responsibility, and wisdom. These values resonate in the oral traditions of the Gorontalo people, providing clear guidelines for managing mosque finances. Moreover, the research highlights a critical need for enhanced information transparency to the public, essential for maintaining the congregation's trust and fostering a stronger community connection.